The impacts of distinct light spectra on the growth properties and maternal productivity of rats - Tirasci, N.; Simsek, U. G. (Hellenic Veterinary Medical Soc, 2025)
The aim of this study is to determine how the complete visible light spectrum and white light affect the growth characteristics of rat puppies, oxidative stress measures, and maternal productivity. In the study, a total of 56 female and 28 male breeding rats ( Sprague Dawley) were mated, with 8 female and 4 male rats in each group. Their growth characteristics were followed until the 63rd day. At the end of the study, 4 female and 4 male rats from each group were euthanized under anesthesia. Oxidative stress parameters were determined in their blood samples. The green lighting group had the highest puppy yield and weaning rate. The blue lighting group had the highest live weight and live weight gain during the suckling period. The red and green lighting groups had the highest pubertal weights. The highest feed consumption rate was obtained in the green lighting group. Feed utilization and water consumption were similar among the lighting groups. The white lighting group had the highest level of total antioxidant status (TAS), while the red lighting group had the lowest TAS level. The highest levels of total oxidant status (TOS) and oxidative stress index (OSI) were found in the red lighting group. These results suggested that the rats were affected differently by the light spectrum at different physiological periods.
Keywords: Rat; visible spectrum; lighting; fertility; growth